Frontline intensive chemotherapy improves outcome in young, high-risk patients with follicular lymphoma: pair-matched analysis from the Czech Lymphoma Study Group Database - Procházka, Vít; Papajík, Tomáš; Janíková, Andrea; Belada, David; Kozák, Tomáš; Šálek, David; Sýkorová, Alice; Móciková, Heidi; Campr, Vít; Dlouhá, Jitka; Langová, Kateřina; Fürst, Tomáš; et al. (Leukemia & lymphoma, 2017)
Optimal frontline treatment in younger high tumor-burden risk follicular lymphoma patients remains a challenge given the reduced efficacy of standard immunochemotherapy (R-CHOP) in widespread disease and unclear role of intensive induction. The retrospective non-randomized pair-matched (1:3) analysis compared 48 intermediate/high Follicular Lymphoma International Prognostic Index (FLIPI) patients receiving intensive rituximab sequential chemotherapy (R-SQ) with 144 random controls (R-CHOP) matched for age, FLIPI score, and maintenance delivery. Complete response rates were 91.7% and 74.1%, respectively (p = .038). After a median follow-up of 8.8 (R-SQ) and 6.5 years (R-CHOP), 5-year time to treatment failure, progression-free survival, and overall survival were 80.9%, 83.2%, and 100% and 57.5%, 60.3%, and 92.1% (p = .0044; p = .0047; p = .22), respectively. Intensive treatment was accompanied by higher acute hematologic toxicity and infections, comparable non-hematologic toxicity, and incidence of secondary malignancies. Intensive induction demonstrates superior long-term disease control compared to R-CHOP, with higher acute hematologic toxicity, but without acute treatment-related mortality. Further studies are needed to define ultra-high-risk FL patients benefiting most from treatment intensity.
Keywords: senioři; Population Surveillance; udržovací chemoterapie; prognosis; follicular lymphoma; Remission Induction; Neoplasm Grading; Česká republika; výsledek terapie; Middle Aged; mužské pohlaví; Autologous transplantation; Adult; Lymphoma, Follicular; Czech Republic; surveillance populace; věkové faktory; Neoplasm Staging; ženské pohlaví; Humans; Tumor Burden; tumor burden; chemotherapy; analýza párové shody; lidé středního věku; stupeň nádoru; Matched-Pair Analysis; Antineoplastic Combined Chemotherapy Protocols; indukce remise; Maintenance Chemotherapy; Age Factors; staging nádorů; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; folikulární lymfom; Treatment Outcome; lidé; Male